2021
DOI: 10.1111/ijlh.13448
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the new hematology analyzer UniCel DxH 900

Abstract: Introduction UniCel DxH900 (Beckman Coulter, Miami, Florida, USA) is a quantitative, multi‐parameter, automated hematology analyzer for in vitro diagnostic use in clinical laboratories. The aim of this study was to evaluate the analytical performance of the new DxH900 analyzer to verify its diagnostic and clinical utility in the hematology laboratory of a tertiary care hospital in Spain. The most important and novel feature offered by DxH900 analyzer is providing MDW (monocyte distribution width), a new hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The Coulter principle, under the VCSn (volume, conductivity, and scatter) technology, 6 could provide quantitative measurement information of the blood cell morphology (including cell size, morphology and lobulation of nucleus, intracellular granules, etc.). Monocyte distribution width (MDW), a parameter provided by the aforementioned DxH800/900 cellular analysis system, reflects the variability and heterogeneity of monocyte size in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…The Coulter principle, under the VCSn (volume, conductivity, and scatter) technology, 6 could provide quantitative measurement information of the blood cell morphology (including cell size, morphology and lobulation of nucleus, intracellular granules, etc.). Monocyte distribution width (MDW), a parameter provided by the aforementioned DxH800/900 cellular analysis system, reflects the variability and heterogeneity of monocyte size in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…Monocyte distribution width (MDW), a novel biomarker for sepsis detection, is a measure of the dispersion around the mean of monocyte population volume, which is estimated with the volume, conductivity, and scatter technology ( 3 ). In the early phase of sepsis, MDW manifests with changes in its functional and morphologic properties—resulting in a highly heterogeneous population—in response to proinflammatory signals from pathogen-associated molecular patterns ( 4 ).…”
mentioning
confidence: 99%
“…In 2017, a survey of 1500 laboratories by the National Center for Clinical Laboratories of China showed that less than 3% of laboratories conducted plasma PC activity testing. In order to ameliorate this situation, this study established a PC detection system based on the chromogenic substrate method, conducted preliminary performance evaluation, and comparison with Siemens detection system 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…In order to ameliorate this situation, this study established a PC detection system based on the chromogenic substrate method, conducted preliminary performance evaluation, and comparison with Siemens detection system. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%